THE MOVEMENT AND MIXING OF DISPERSED MATERIALS IN ROTARY FURNACES - S. L. Rovin; L. E. Rovin; V. A. Zharanov; V. S. Mazurov (Литьë и металлургия, 2017)
This article describes motion and heat and mass transfer in the layer of dispersed material in a rotary furnace. Presents the results of a comprehensive study of these processes, including pilot studies, computer modeling and simulation, which allow to optimize the design and process parameters of rotary furnaces.